Investigating Factors Affecting Group Processes in Virtual Learning Environments. (March 2015) - Hazari, Sunil; Thompson, Sandra
With the widespread popularity of distance learning, there is a need to investigate elements of online courses that continue to pose significant challenges for educators. One of the challenges relates to creating and managing group projects. This study investigated business students' perceptions of group work in online classes. The constructs of learning and social interaction, process satisfaction, product satisfaction, and use of technology in the virtual learning environment were investigated. The use of social media networks by group participants was also examined. Recommendations are provided for business educators looking to develop or enhance teamwork in virtual learning environments.